Multistage 8.2 kyr event revealed through high‐resolution XRF core scanning of Cuban sinkhole sediments. Issue 14 (22nd July 2017) - Peros, Matthew; Collins, Shawn; G'Meiner, Anna Agosta; Reinhardt, Eduard; Pupo, Felipe Matos
Abstract: We use sediments from a flooded sinkhole (Cenote Jennifer) in northern Cuba to provide new, well‐dated, high‐resolution evidence for the 8.2 kyr event. From ~7600 to 8700 cal yr B.P. the sinkhole contained shallow, low‐salinity water, which supported a marsh dominated by cattail and grass. Peaks in Cl and Br—occurring at 8150, 8200, and 8250 cal yr B.P.—are attributable to increased evaporation due to regional drying associated with the 8.2 kyr event. The three peaks in these elements also closely correspond to the greyscale record from the Cariaco Basin, indicative of increased upwelling in the southern Caribbean Sea at this time, supporting the notion of a multistage 8.2 kyr event. Our work provides new data that help to clarify the initiation, behavior, and impacts of the 8.2 kyr event in the northern tropics. Key Points: The 8.2 kyr event is characterized by increases in Cl and Br at the study site The increases in Cl and Br are due to enhanced evaporation from regional drying The regional drying occurred in three distinct phases indicating the presence of a multistage 8.2 kyr event in the Caribbean